A Comparative Study of Major Risk Assessment (RA) Frameworks in Geologic Carbon Storage (GCS) - Elvin Hajiyev; Marshall Watson; Hossein Emadi; Bassel Eissa; Athar Hussain; Abdul Rehman Baig; Abdulrahman Shahin (Fuels)
Carbon Capture and Storage (CCS) technology presents a practical solution for reducing industrial carbon dioxide (CO2) emissions through underground anthropogenic CO2 storage in depleted hydrocarbon reservoirs. The long-term storage efficiency faces several CO2 leakage challenges that need to be addressed in the planning phase of the CCS project. Thus, effective risk assessment (RA) methodologies are crucial for ensuring safety, regulatory compliance, and public acceptance of CCS projects. This review examines RA parts and their corresponding technical and non-technical challenges. The analysis critically compares over 20 qualitative, semi-quantitative, quantitative, and hybrid RA techniques employed throughout GCS operations. Available quantitative RA tools do not deliver dependable results because they require technical data that become available late in the CCS project development process. Qualitative approaches work well for the initial screening of storage sites with limited data available, yet quantitative methods enable quantification of CO2 leakage. For the first time, a comparative analysis of two integrated assessment tools is presented in this paper. The techniques achieve success based on high-quality data and analysis of existing technical and non-technical challenges which this paper examines. The comparative analysis outlines the limitations and advantages of every methodology studied and emphasizes the need for integrated hybrid frameworks to boost decision-making in the RA process. Future research should focus on creating or improving existing hybrid frameworks for late-stage RA while utilizing qualitative frameworks in the initial site screening stage to advance GSC’s safe and effective implementation.